The biomechanical and physiological response to repeated soccer-specific simulations interspersed by 48 or 72 hours recovery - Page, R. M.; Marrin, K.; Brogden, K. M.; Greig, M. (Physical Therapy in Sport, 2016)
•Standardised protocols (SSEP) can be used to simulate short-term fixture congestion. •Two SSEPs were interspersed by 48 or 72 h recovery. •A number of physiological and mechanical measures were recorded during the SSEPs. •There was no difference in the fatigue response associated with two SSEPs. •These data have implications for the design and management of activity schedules.